Age, period, cohort effects in trends of depressive symptoms among middle-aged and older Chinese adults - Hu, Xiaoqian; Jin, Wenxue; Wang, Junlei; Dong, Hengjin (Frontiers in Public Health, 2024)
Objectives: To investigate the effects of age, period, and cohort on the trends of depression; and to examine the influence of these three temporal effects on residential disparities in depression.: Using data from the China Health and Retirement Longitudinal Study (CHARLS) during 2011 to 2020, involving 77703 respondents aged 45 years old and above. The measurement of depressive symptoms was the score of 10-question version of the Center for Epidemiologic Studies Depression Scale (CES-D 10). The hierarchical age-period-cohort cross-classified random effects models were conducted to examine trends in depressive symptoms related to age, period and cohort.Results: CES-D scores increased with age and slightly decreased at older age. The cohort trends mostly increased except for a downward trend among those born in 1950s. As for the period effect, CES-D scores decreased gradually from 2011 to 2013 followed by a upward trend. Rural residents were associated with higher level of depression than those live in urban area. These residence gaps in depression enlarged before the age of 80, and then narrowed. The urban-rural disparities in CES-D scores gradually diminished across cohorts, while the corresponding period-based change in urban-rural gaps was not significant.Conclusions: When age, period, cohort factors are considered, the age effects on depression dominated, and the period and cohort variations were relatively small. The residence disparities in depression reduced with successive cohorts, more attention should be paid to the worsening depression condition of younger cohorts in urban areas.